Parâmetros clínicos, hematológicos e bioquímicos de cães naturalmente infectados pelo Parvovirus (PVC- 2) tratados com solução salina hipertônica 7,5% - Fernanda dos Santos Alves (2018)
Canine parvovirus is one of the main causes of hemorrhagic enteritis in dogs and can result in high mortality rates if treatment is not performed quickly and aggressively. In addition, due to its pathophysiological characteristics, parvovirus can result in bacterial translocation and sepsis of enteral origin. The objective of this study was to verify the clinical characteristics of dogs infected with parvovirus (PVC-2), correlating them with the occurrence of death and with the use ofhypertonic saline 7.5%. For this, the present study was carried out in two stages, the first one consisted of a retrospective study of 101 cases of parvovirus treated at the Veterinary Hospital of the Universidade Federal de Minas Gerais from 2014 to 2017. This stage generated three resultsthesis. In the first one, it is concluded that the prognosis of canine parvovirus is altered with the sequence of days of hospitalization, being no longer reserved for the unfavorable after the fourth day, in order to become reserved in favor of the other days of hospitalization. Additionally, the association of these data with the results of the physical parameters heart rate and respiratory and systolic blood pressure, makes the prognostic evaluation more accurate. In the second chapter, it is concluded that there is an intense correlation of the leukocyte count of the hemogram performed on the day of admission to the veterinary hospital with the mortality, with the mortality being higher in intensely leucopenic animals. There is a tendency to increase the percentage andconcentration of toxic neutrophils during the first five days of hospitalization, probably associated with secondary bacterial infections. In the hemogram of admission at the veterinary hospital, the animals tend to present anemia masked by dehydration, which, after the establishment of fluid therapy, results in mild to moderate anemia. In the platelet of intensely leucopenic animals there is a tendency to fall in the platelet count in the first two days of hospitalization, resulting in discrete thrombocytopenia. In the third chapter, a statistical study was performed on the correlation of death with the physical, hematological, biochemical and hemogasometric parameters. The second stage of the present thesis consisted of a clinical experiment in which 24 dogs positive for canine parvovirosis were randomly distributed in three groups, with G1 animals receiving the standard treatment for the disease, G2 receiving, in addition to the standard treatment, two applications of hypertonic saline 7.5% and G3 one more application of hypertonic saline (HS). This step generated two chapters of results of the present thesis, which correlated the different treatments with the hematological profile and serum biochemistry. As a result, no hematological or serum biochemical changes were consistently correlated with HS use.